Underlying evidence for the health benefits of fermented foods in humans. Issue 9 (6th April 2022) - Rul, F.; Béra-Maillet, C.; Champomier-Vergès, M. C.; El-Mecherfi, K. E.; Foligné, B.; Michalski, M. C.; Milenkovic, D.; Savary-Auzeloux, I.
Abstract : Fermented foods (FFs) have been a part of our diets for millennia and comprise highly diverse products obtained from plants and animals all over the world: Mechanisms of action and impact of health status. Abstract : Fermented foods (FFs) have been a part of our diets for millennia and comprise highly diverse products obtained from plants and animals all over the world. Historically, fermentation has been used to preserve food and render certain raw materials edible. As our food systems evolve towards more sustainability, the health benefits of FFs have been increasingly touted. Fermentation generates new/transformed bioactive compounds that may occur in association with probiotic bacteria. The result can be specific, advantageous functional properties. Yet, when considering the body of human studies on the topic, whether observational or experimental, it is rare to come across findings supporting the above assertion. Certainly, results are lacking to confirm the widespread idea that FFs have general health benefits. There are some exceptions, such as in the case of lactose degradation via fermentation in individuals who are lactose intolerant; the impact of select fermented dairy products on insulin sensitivity; or the benefits of alcohol consumption. However, in other situations, the results fail to categorically indicate whether FFs have neutral, beneficial, or detrimental effects on human health. This review tackles this apparent incongruity by showing why it is complex to test the health effects of FFs and what can be done to improve knowledge in this field.